2008
DOI: 10.1002/macp.200700283
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Arrangement of L‐Lactide and D‐Lactide in Poly[(L‐lactide)‐co‐(D‐lactide)] on its Resistance to Hydrolysis Studied by Molecular Modeling

Abstract: Molecular modeling is used to explain how the resistance of poly[(L‐lactide)‐co‐(D‐lactide)] to hydrolysis is affected by the percentages of L‐ and D‐lactide and their arrangements in blocks or random arrangements in the polymer. Previous studies on improving the hydrolysis resistance of PLA have involved forming either poly(L‐lactide)/poly(D‐lactide) (PLLA/PDLA) polyblends or copolymers of L‐ and D‐lactide. In this study, molecular modeling was used to study the hydrolysis resistance of PLA containing various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 26 publications
(44 reference statements)
3
16
0
Order By: Relevance
“…The M n values were higher for the P(L-2HB)/P(D-2HB) blend than for pure P(L-2HB) and P(D-2HB), when compared for the same degradation periods. The remaining weight percentages and M n values reflect that the P(L-2HB)/P(D-2HB) blend has a superior hydrolytic degradation resistance as compared with pure P(L-2HB) and P(D-2HB); this is in agreement with the experimental results of hydrolytic degradation [16][17][18][19] and theoretical calculations 34 for a PLLA/PDLA stereocomplex relative to pure PLLA and PDLA. The value of M w /M n of pure P(L-2HB), P(D-2HB) and their blend increased in the first 8 days, followed by a decrease or plateau.…”
Section: Hydrolytic Degradationsupporting
confidence: 87%
“…The M n values were higher for the P(L-2HB)/P(D-2HB) blend than for pure P(L-2HB) and P(D-2HB), when compared for the same degradation periods. The remaining weight percentages and M n values reflect that the P(L-2HB)/P(D-2HB) blend has a superior hydrolytic degradation resistance as compared with pure P(L-2HB) and P(D-2HB); this is in agreement with the experimental results of hydrolytic degradation [16][17][18][19] and theoretical calculations 34 for a PLLA/PDLA stereocomplex relative to pure PLLA and PDLA. The value of M w /M n of pure P(L-2HB), P(D-2HB) and their blend increased in the first 8 days, followed by a decrease or plateau.…”
Section: Hydrolytic Degradationsupporting
confidence: 87%
“…Similar to this result, P(LLA-co-CL) retained a higher molecular weight than P(DLLA-co-CL) during NHD [155]. Karst and Yang [295] used molecular modeling to explain the fact that resistance of stereocopolymers poly(L-lactideco-D-lactide) P(LLA-DLA) to hydrolysis is affected by the percentages of L-and D-lactyl units and their arrangement (block or random) in the polymer. It was found that among the stereocopolymers with the longest blocks of L-and Dlactyl units, those containing 50% L-lactyl units had greater hydrolysis resistance and were more stable before hydrolytic degradation compared to stereocopolymers with 26% or 74% L-lactyl units.…”
Section: Molecular Structuresupporting
confidence: 70%
“…A similar result was obtained for the alkaline hydrolytic degradation of PLLA/PDLA blend monolayers [233]. Molecular modeling ascribed the high hydrolysis resistance of PLLA/PDLA blends compared to that of stereocopolymers P(LLA-DLA) with the same L-lactyl unit content to the fact that blends can form more stereocomplexes than stereocopolymers [295].…”
Section: Highly Ordered Structuressupporting
confidence: 65%
“…Since the gradual left-hand shift of the phase curve means that the critical gelation concentration was decreased due to an increased density of hydrophobic core and decrease in water solubility with increasing amount cross-linked ratio PL(D)LA. This can be related to the structural stability of individual micelles that were closely packed to form a three dimensional gel structure due to an increase in crystallinity or chain packing tendency at critical concentration and temperature [19]. The stereocomplexed crystallites produced from the complexation of enantiomeric copolymer based on PLLA and PDLA should have physically cross-linked copolymers, resulting in more robust and stable Pluronic based sol-gel transition hydrogels.…”
Section: Scheme I Synthesis Of Cross-linked Pl(d)la-pluronic Copolymentioning
confidence: 99%